2016
DOI: 10.1101/gr.197194.115
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer methylation dynamics contribute to cancer plasticity and patient mortality

Abstract: During development, enhancers play pivotal roles in regulating gene expression programs; however, their involvement in cancer progression has not been fully characterized. We performed an integrative analysis of DNA methylation, RNA-seq, and small RNA-seq profiles from thousands of patients, including 25 diverse primary malignances and seven body sites of metastatic melanoma. We found that enhancers are consistently the most differentially methylated regions (DMR) as cancer progresses from normal to primary tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
78
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 59 publications
(69 reference statements)
9
78
0
Order By: Relevance
“…To prioritize enhancers which may possibly regulate gene expression among all enhancers marked by active epigenomic marks, we first identified ~50,000 probes (located within nucleosome-depleted subregions of enhancers) that are differentially methylated in breast, prostate, and kidney tumors, as compared to normal tissues; these probes correspond to ~25,000 different enhancer regions that have gained or lost activity in the tumor tissues. Because previous studies have shown a significant association between the DNA methylation level of an enhancer and the expression level of a direct target gene of the enhancer [27, 28], we then developed an approach (TENET) that identifies statistically significantly associated relationships (links) between DNA methylation and gene expression genome-wide using raw p values by calculating z scores, empirical p values, and Wilcoxon rank sum test p values. Although the number of enhancer to gene links can vary depending on the settings of cut-offs, in general, when we linked gene expression levels with enhancer activity, we found that only ~20% of the enhancer probes show a positive relationship between activity state and expression of a gene.…”
Section: Discussionmentioning
confidence: 99%
“…To prioritize enhancers which may possibly regulate gene expression among all enhancers marked by active epigenomic marks, we first identified ~50,000 probes (located within nucleosome-depleted subregions of enhancers) that are differentially methylated in breast, prostate, and kidney tumors, as compared to normal tissues; these probes correspond to ~25,000 different enhancer regions that have gained or lost activity in the tumor tissues. Because previous studies have shown a significant association between the DNA methylation level of an enhancer and the expression level of a direct target gene of the enhancer [27, 28], we then developed an approach (TENET) that identifies statistically significantly associated relationships (links) between DNA methylation and gene expression genome-wide using raw p values by calculating z scores, empirical p values, and Wilcoxon rank sum test p values. Although the number of enhancer to gene links can vary depending on the settings of cut-offs, in general, when we linked gene expression levels with enhancer activity, we found that only ~20% of the enhancer probes show a positive relationship between activity state and expression of a gene.…”
Section: Discussionmentioning
confidence: 99%
“…Microenvironmental hypoxia has been shown to suppress DNA demethylase activity in breast cancer (97). Altered cellular contexts can also increase the rate of DNA methylation changes that affect enhancer activity and increase transcriptional plasticity in melanoma (98). Finally, the observation that non-malignant cells in the tumor ecosystem can also undergo striking phenotypic changes suggests that microenvironmental effects on epigenetic states and plasticity may extend beyond the malignant compartment (99).…”
Section: Non-genetic Stimuli Of Plasticity or Restrictionmentioning
confidence: 99%
“…Evasion of growth suppressors, such as p16/INK4a, can be mediated by promoter hyper-methylation or EZH2 hyperactivity (3, 35). Invasion and metastasis depend on cell fate transitions, such as epithelial-mesenchymal transition (EMT), with epigenetic etiology (98, 102104). Replicative immortality may be driven by mutations to histone H3.3 or its chaperone proteins that promote alternative telomere lengthening (65, 105), or by non-genetic mechanisms that simulate self-renewing stem cell states (9, 106).…”
Section: The Hallmarks Of Cancermentioning
confidence: 99%
“…A significant correlation was found between specific enhancer methylation patterns and patient survival. Specifically, differential methylation of KIT-, CYTL1-, and KIF14-associated enhancers played a role in regulating proliferation [121]. …”
Section: Differential Dna Methylation As a Biomarker In Melanomamentioning
confidence: 99%